Morphology and geochemical signatures of diatexite migmattes around Mararaban Liman Katagum, Bauchi State, North Eastern Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2025)
The Migmatites of the study area fall under the older granite that constitutes the Basementcomplex of Nigeria. The aim of this research is to present the result of a geochemicalinvestigation of Migmatites in the study area. Diatexite migmatites, which include melano-cratic, mesocratic, and leucocratic diatexites covered almost all of the study area, aroundMararaban Liman Katagum, Bauchi, in North-eastern Nigeria. Geochemically, these rocksshow high SiO2 in the range of 65.81–83.12wt% with an average of 74.43wt%, Al2O3 andFeO3 enrichment are pronounced in the rock samples ranging from 10.02 to 13.80 and1.06 to 11.21 showing an average of 12.59wt% and 11.05wt%, respectively. In addition,Na2O remains consistently less than K2O in the range of 0.06–1.84 and 0.6–6.4 respec-tively in most of the samples. The rocks are generally depleted in CaO, SO3, MgO, P2O5,and MnO in the range of 0.02–0.82, 0.005–1.23, 0.01–3.84, 0.006–0.16, and 0.004–0.21,respectively. They are peraluminous with S-type characteristics, magnesian to ferroan.The diatexite migmatites show a clear arc-like signature as seen in the depletion in highfield strength elements (HFSE) and enrichment in large ion lithophile elements (LILE), andLILE enhancement relative to HFSE signifies subduction-zone enrichment and/or crustalmixing of the source region.